Development of a matching framework for voluntary services provided to home-dwelling older adults by nursing faculty and students based on the Kano model - Lei Huang; Weihong Yang; Lina Wang; Pei Wang; Yan Lin; Shuyao Hui; Peng Wang; Xiang Sun; Yue Yao; Rui Chen; Fengjian Zhang; Lulu Liao; et al. (BMC Nursing)
Abstract Background As population aging accelerates, volunteer services provide meaningful community support for older adults. However, evidence is limited on how to align their needs with the service intentions of nursing faculty and students to develop appropriate frameworks. Methods Data were collected through self-designed demand-supply matching questionnaires from nursing faculty and students (March 26 - April 25, 2023) and older adults (May 24 - July 7, 2023) using convenience sampling. Results This study, based on the principle of demand-supply matching, identified volunteer service items that home-dwelling older adults expect to receive and that nursing faculty and students are not opposed to providing. These services span environmental support, physiological care, psychosocial support, and health-related behaviors. Through prioritization, a three-tiered demand-supply matching framework was established, consisting of basic services, expected services, and optional services. Conclusions This study applies the Kano model to explore the expectations of urban home-dwelling older adults and the service intentions of nursing faculty and students, identifying key commonalities and differences. Reverse attributes highlight the importance of respecting privacy, autonomy, and trust in volunteer services. The demand-supply matching questionnaire and service framework developed in this study can assist nursing faculty and students willing to volunteer by providing detailed evaluations and strategic guidance for selecting appropriate services and implementation order. This contributes to cultivating a professional, responsive nursing volunteer workforce and advancing China’s Healthy China strategic goals. Clinical trial number Not applicable.